THE FRUIT OF MAY: HISTORIC REVIEW OF STUDENT MOVEMENT IN LATIN AMERICA IN THE BEGINNING OF THE TWENTIETH CENTURY - Lima Jardilino, José Rubens (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
In this article, I intend to review the issues of social history of student movements on the continent, focusing on Argentina, Peru, Cuba and Mexico. Of course, I do it in full partnership with specialists with whom I maintain intensive dialogue about my narrative on the subject. In France, even with the Socialists in power, there was a defacement work of the movement soon after its end. May 68 was definitively established as youth´s revolt or youth´s love time. The movement of 1968 was like an aspiration of young people seeking to abolish the father´s yoke and sexual taboos. Moreover, we must recognize the French cultural content movement and its strong desire to change the institutional structures of modernity - University, family, pointing it as a social movement that align strong partnerships between farmers and workers in the fight for a culture change. There are also some who say that its legacy has left only the weight of drugs to a postmodern and esoteric world. In front of this diversity of visions, we take the freedom to understand the movement of “half-eight” in a historical perspective of the role of youth, who claimed changes in social structures since the beginning of the century.